Progression of motor subtypes in Huntington’s disease: a 6-year follow-up study - Jacobs, M. (J Neurol, 2016)
The objective of this study is to investigate the progression of predominantly choreatic and hypokinetic-rigid signs in Huntington’s disease (HD) and their relationship with cognitive and general functioning over time. The motor signs in HD can be divided into predominantly choreatic and hypokinetic-rigid subtypes. It has been reported in cross-sectional studies that predominantly choreatic HD patients perform better on functional and cognitive assessments compared to predominantly hypokinetic-rigid HD patients. The course of these motor subtypes and their clinical profiles has not been investigated longitudinally. A total of 4135 subjects who participated in the European HD Network REGISTRY study were included and classified at baseline as either predominantly choreatic (n = 891), hypokinetic-rigid (n = 916), or mixed-motor (n = 2328), based on a previously used method. The maximum follow-up period was 6 years. The mixed-motor group was not included in the analyses. Linear mixed models were constructed to investigate changes in motor subtypes over time and their relationship with cognitive and functional decline. Over the 6-year follow-up period, the predominantly choreatic group showed a significant decrease in chorea, while hypokinetic-rigid symptoms slightly increased in the hypokinetic-rigid group. On the Total Functional Capacity, Stroop test, and Verbal fluency task the rate of change over time was significantly faster in the predominantly choreatic group, while on all other clinical assessments the decline was comparable for both groups. Our results suggest that choreatic symptoms decrease over time, whereas hypokinetic-rigid symptoms slightly increase in a large cohort of HD patients. Moreover, different motor subtypes can be related to different clinical profiles. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00415-016-8233-x) contains supplementary material, which is available to authorized users.